The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000476035
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences and Effects of Environmental Manipulation on Astrocytes (Glial Fibrillary Acidic Protein), Glucocorticoid Receptor, and Microglia (Iba1) Immunoreactivity between Wistar-Kyoto and Wistar Females

Abstract: Background: Depression is often associated with an increase in hypothalamic-pituitary-adrenal (HPA) axis reactivity and immune response. To investigate this relationship, we examined the consequences of environmental manipulation on the neural correlates of the HPA axis and immune response in an animal model of depression, the Wistar-Kyoto (WKY) rat. Additionally, female animals are often overlooked in preclinical research because of the hormone fluctuations inherent in the estrous cycle. Methods: Female rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The possible impaired negative feedback in WKY rats does not appear to be due to a downregulation of glucocorticoid receptors (GRs) [ 81 , 82 ]. In contrast, increased GR staining in the hippocampus of WKY females compared to Wistars, and increased expression of hippocampal Nr3c1 (GR) in WKYs compared to SD, suggest upregulation of GRs in WKYs [ 101 , 102 ]. The upregulation of hippocampal GR in the WKYs parallels the antidepressant effects of glucocorticoid synthesis inhibitors and GR antagonists [ 103 - 105 ], while the findings of GR downregulation could be specific to peripheral cells in major depressive disorder (MDD) individuals [ 99 ].…”
Section: Physiological Phenotypesmentioning
confidence: 99%
“…The possible impaired negative feedback in WKY rats does not appear to be due to a downregulation of glucocorticoid receptors (GRs) [ 81 , 82 ]. In contrast, increased GR staining in the hippocampus of WKY females compared to Wistars, and increased expression of hippocampal Nr3c1 (GR) in WKYs compared to SD, suggest upregulation of GRs in WKYs [ 101 , 102 ]. The upregulation of hippocampal GR in the WKYs parallels the antidepressant effects of glucocorticoid synthesis inhibitors and GR antagonists [ 103 - 105 ], while the findings of GR downregulation could be specific to peripheral cells in major depressive disorder (MDD) individuals [ 99 ].…”
Section: Physiological Phenotypesmentioning
confidence: 99%
“…This suggests that the significant increase in CORT levels previously seen may be due to hyperactivity of the HPA axis when handling and/or blood sampling. That being said, studies have reported altered density of GRs in the WKY rat 34,35 and decreased GR function contributes to HPA axis hyperactivity and the development of depressive symptoms, 36 which may account for the depressive‐like phenotype seen in these rats.…”
Section: Discussionmentioning
confidence: 99%